MENINGKATKAN KEMAMPUAN SISWA MEMBACA AL-QUR’AN MELALUI PENGGUNAAN MEDIA KARTU PERMAINAN KUARTET TAJWID DI TINGKAT X SMK NEGERI 1 TANJUNG - Aserani Aserani (Vidya Karya, 2013)
This study aims to increase motivation of tenth grade students of SMKN 1 Tanjung in learning Tajwid by using playing card media called “Kuartet Tajwid”. Research subjects are Al Quran education teacher and tenth grade students of SMKN 1 Tanjung. Research was conducted in two cycles, where each scycle consists of 2 lessons. The data are get by using observation sheet, questioner, and test. The data was analyzed by using descriptive analysis technique. The research shows that (1) Application of “Kuartet Tajwid” media increases motivation of tenth grade students of SMKN 1 Tanjung in learning Al Quran, (2) By applicating “Kuartet tajwid, student activation in learning Al Quran is getting better and more increase (3) Practically, application of “Kuartet Tajwid” in learning Al Quran education increases students abilition to read Al-Qur’an based on the tajwid.